On the Axiomatic Foundation of Ecological Footprint Indices - Thomas Kuhn; Radomir Pestow; Anja Zenker (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2018)
The objective of this paper is to provide an axiomatic foundation to the concept of ecological footprint indices. For this purpose, we propose five axioms representing general properties which any ecological footprint measure should fulfill. It can be shown that there exists a unique index which is characterized by the given set of axioms. Its functional form is determined and an economic interpretation is given. We find that the proposed index may resolve or confirm some important issues discussed in the literature. First, it incorporates a trade component indicating the ecological footprint of economic activities embodied in the trade pattern of a country or region. Moreover, the productivity of land use in production as a means to mitigate the pressure on the ecological system is reflected. But most importantly, from a methodological point of view, there is no longer the need for designing ecological footprint indices ad-hoc, in particular for the sake of empirical application.
Keywords: Q01; Q20; Q30; C43; 330; Ecological Footprint Index; Axiomatic Foundation; Sustainable Welfare; Economic Inequality